2021
DOI: 10.3390/su13031460
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Biochar on Soil and Water Loss on Sloping Farmland in the Black Soil Region of Northeast China during the Spring Thawing Period

Abstract: Biochar, as a kind of soil amendment, has attracted wide attention from scholars in various countries, and the effects of biochar on soil and water loss have been well reported. However, soil erosion is significantly affected by geographical conditions, climate, and other factors, and research on the characteristics of soil erosion and the effects of biochar application in seasonally frozen soil areas is currently unclear. The purpose of this study was to explore the effect of corn straw biochar application on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…PFM increased the farmland infiltration rate, which was similar to the research results that some porous materials (such as biochar, straw, and PAM) applied in the farmland (Abrol et al, 2016;Wang et al, 2017). Porous fiber materials changed some soil physical and hydrological characteristics such as soil porosity, water conductivity, aggregate stability, and that the materials including huge pores could provide sufficient space for water storage during rainfall, which benefits the soil infiltration rate increased and reached stable infiltration faster (Gholami et al, 2019;Yu et al, 2021). In the early stage of a rainfall event, the PFM water content was often lower than the soil water content in the same depth, which would make soil water suction in the PFM groups higher than the control groups during rain.…”
Section: Porous Fiber Materials Influence the Infiltration And Runoffsupporting
confidence: 83%
See 2 more Smart Citations
“…PFM increased the farmland infiltration rate, which was similar to the research results that some porous materials (such as biochar, straw, and PAM) applied in the farmland (Abrol et al, 2016;Wang et al, 2017). Porous fiber materials changed some soil physical and hydrological characteristics such as soil porosity, water conductivity, aggregate stability, and that the materials including huge pores could provide sufficient space for water storage during rainfall, which benefits the soil infiltration rate increased and reached stable infiltration faster (Gholami et al, 2019;Yu et al, 2021). In the early stage of a rainfall event, the PFM water content was often lower than the soil water content in the same depth, which would make soil water suction in the PFM groups higher than the control groups during rain.…”
Section: Porous Fiber Materials Influence the Infiltration And Runoffsupporting
confidence: 83%
“…However, biochar was easy to be washed off by runoff or block the soil pores in some extreme rainfall events, which led to the intensification of farmland floods (Peng et al, 2016). But PFM does not have the above shortcomings in practical application due to the difference in its layout mode (Yu et al, 2021). In nature, the formation and growth of surface runoff depend more on the relationship between rainfall intensity and soil infiltration rate (Zhao X. et al, 2014;Werdin et al, 2021).…”
Section: Porous Fiber Materials Influence the Infiltration And Runoffmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that planting high-quality forage is an important measure to improve the quality and fertility of degraded arable soils (Yu et al, 2021). Meanwhile, a previous study observed improvements in field, pest management, and soil fertility with crop rotations.…”
Section: Introductionmentioning
confidence: 99%